"Bubble wrapping vs. helping him learn his way": gender and definitions of parenting through the case of infertility. Issue 1 (2nd January 2020) - Bell, Ann V.
ABSTRACT: Researchers deem gender a fundamental organizing principle of parenting. Men and women not only have distinct roles of fathers and mothers, but also perform those roles according to norms of masculinity and femininity. Recently, however, such distinctions are converging. Fathers are no longer the distant male breadwinner of the past; they are now aligned with stereotypically feminine traits of caring, gentleness, and involvement in the "new, nurturant" fatherhood. While cultural images abound, there is little understanding of how individuals themselves make sense of parenting. I explore such understanding using the case of infertility. To do so, I compare men's definitions of fatherhood to women's conceptions of motherhood, revealing the significance of gender to their meaning-making. Indeed, even with shifting social ideologies, important gender differences in parenting remain. Through interviews with white, high-income individuals in the US who are struggling with their reproduction ( n = 43), I find that nurturing is at the center of women's understandings of motherhood in which self-sacrifice is prominent. In contrast, men distance themselves from this caretaker role by constructing their time spent with children in masculine ways. In other words, men leave the "nurturing" to women and have redefined the nurturant father to maintain parenting as gendered.